Flying a Micro-Drone by Dynamic Charging for Vertical Direction Using Optical Wireless Power Transmission - Tomoya Watamura; Takuo Nagasaka; Yuto Kikuchi; Tomoyuki Miyamoto (Energies)
Micro-drones weighing less than about 200 g have a limited flight time of 5–15 min. Dynamic charging by optical wireless power transmission is a promising solution to this problem. This paper investigated the configuration and conditions required for dynamic charging of micro-drones by optical wireless power transmission and clarified the effect of weight change on the power required for flight and the size of solar cells that can be installed. Furthermore, a micro-drone equipped with a solar cell without a battery was used to demonstrate a vertical flight height of 75 cm at 35 W light output. The results are useful for continuous flight of micro-drones by optical wireless power transmission.